(untitled) (Philology, 2024)
Advertising messages of the Taisho era on one hand reflected the life of the new middle class in a rapidly changing urban world and on the other hand influenced the public consciousness by offering appropriate to the era images and behaviours. Advertising was a guide to the “brave new world”, advertising posters and texts enlightened the masses, telling the consumer about their options. Under the influence of advertising, the culture of mass consumption was formed. Advertising gives symbolic significance to ordinary things, creates new communicative patterns, ideals, standards. The diachronic analysis of advertising messages of the Taisho era helps us trace the mutual influence of advertising and the processes taking place in society and this is the principal value of the research. The object of the study is advertising of the Taisho era. The main aim is to reveal the impact of the advertising to consumer and society of this period using content analysis methods. The author comes to conclusion that the advertising of the Taisho era became an entertainment genre; the value of all sorts of elements of suggestive impact and interactivity increased during the Taisho era. The development of graphic design of Japanese advertising in the XX century passed similar stages in comparison with the development of advertising design in Western countries. The Japanese advertising has features inherent in the discourse of the modern and postmodern era. Meanwhile, the content of advertising messages has national and cultural specificity.